Anti-tumour necrosis factor treatment in patients with refractory systemic vasculitis associated with rheumatoid arthritis. Issue 6 (23rd November 2007) - Puéchal, X; Miceli-Richard, C; Mejjad, O; Lafforgue, P; Marcelli, C; Solau-Gervais, E; Steinfeld, S; Villoutreix, C; Trèves, R; Mariette, X; Guillevin, L; ,
Abstract : Objective: To assess anti-tumour necrosis factor (anti-TNF) agents in patients with refractory systemic rheumatoid vasculitis (SRV). Methods: 1200 rheumatologists and internists were asked to provide medical files for patients with anti-TNF agents given as a second-line treatment for active SRV refractory to cyclophosphamide and glucocorticoids. Results: We identified nine cases in which anti-TNF drugs were given for active SRV, despite previous treatment with a mean cumulative dose of 8.4 g of cyclophosphamide in association with high-dose glucocorticoids. The mean prednisone dose before anti-TNF therapy was 29.6 mg/day. After 6 months, six patients were in remission (complete in five, partial in one). The treatment failed in one patient and two patients stopped taking the anti-TNF treatment due to side-effects. Mean prednisone dose was reduced to 11.2 mg/day. Severe infection occurred in three patients. Relapses were observed in two patients. Remission was re-established by reintroducing anti-TNF therapy in one case and increasing the dose in the other. Conclusions: This study provides evidence of efficacy of anti-TNF therapy in adjunct to glucocorticoids for treating active refractory SRV. Remission was achieved in two-thirds of patients, with a significant decrease in prednisone dose, although there was a high rate of infection in these severely ill patients.